Comprehensive studies of defect production and strained states in silicon epitaxial layers and device structures based on them - Boltovets, N.S.; Voitsikhovskyi, D.I.; Konakova, R.V.; Milenin, V.V.; Makara, V.A.; Rudenko, O.V.; Mel’nichenko, M.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2001)
Using the Lang technique of x-ray topography, double-crystal x-ray spectrometry and selective chemical etching, we investigated the defect production in silicon epitaxial structures grown on the n⁺-Si substrates (surface finish classes 12 and 14). Correlation has been revealed between the reverse current of thermal-generation nature, minority charge carrier lifetime τp in the n-layer and concentration of structural defects (structural perfection of the n⁺-substrate). We advance a model for strained state of multilayer device structures, in particular, those with ohmic and contact layers.